2010
DOI: 10.1111/j.1439-0450.1981.tb01774.x
|View full text |Cite
|
Sign up to set email alerts
|

Light Microscopy and Ultrahistology of Intestinal Changes in Pigs Infected with Epizootic Diarrhoea Virus (EVD): Comparison with Transmissible Gastroenteritis (TGE) Virus and Porcine Rotavirus Infections

Abstract: For almost three decades, transmissible gastroenteritis virus (TGE), a coronavirus, was the only known viral agent to cause severe neonatal diarrhoea in pigs, giving rise to considerable losses (1). Recently, a number of other viruses have been shown to be involved in the aetiology of diarrhoea in pigs, namely rotaviruses (9, 1 l), the epizootic diarrhoea virus (another coronaviruslike agent not related to TGE virus,4,8,14), rotavirus-like, calici-virus-like and 23 nm virus-like particles (18). Present evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…The infection and pathogenic features of classical PEDV CV777 strain were examined in earlier studies (Table 4) (Coussement et al, 1982;De Bouck et al, 1981;Debouck and Pensaert, 1980;Ducatelle et al, 1981;Pospischil et al, 1981). One to twenty day-old cesarean-derived, colostrum-deprived (CDCD) and conventional piglets inoculated with PEDV CV777 had clinical signs between 23 and 40 h post-inoculation (HPI) (Coussement et al, 1982;Debouck and Pensaert, 1980).…”
Section: Classical Pedv Infections Cause Acute Gastroenteritis and Inmentioning
confidence: 99%
“…The infection and pathogenic features of classical PEDV CV777 strain were examined in earlier studies (Table 4) (Coussement et al, 1982;De Bouck et al, 1981;Debouck and Pensaert, 1980;Ducatelle et al, 1981;Pospischil et al, 1981). One to twenty day-old cesarean-derived, colostrum-deprived (CDCD) and conventional piglets inoculated with PEDV CV777 had clinical signs between 23 and 40 h post-inoculation (HPI) (Coussement et al, 1982;Debouck and Pensaert, 1980).…”
Section: Classical Pedv Infections Cause Acute Gastroenteritis and Inmentioning
confidence: 99%
“…Isolates in the outbreak in China had only a minor nucleotide sequence variation from the Thailand isolates, indicating that the virus has a high genetic relatedness to the Southeast Asia strain. However, previous studies showed that isolates from Europe, South Korea, and China were serologically identical to the prototype CV777 strain ( 1 , 4 ). …”
mentioning
confidence: 92%
“…Replication was mainly localized in the cytoplasm of villous epithelial cells of the small intestine and colon (Sueyoshi et al, 1995). Microscopically, marked cytoplasmic vacuolation and exfoliation of enterocytes with subsequent considerable shortening and fusion of villi were observed (Coussement et al, 1982;Pospischil et al, 1981). However, according to immunohistochemistry (IHC) results reported by Lee et al, PEDV antigens were detected not only in the cytoplasm of the villous enterocytes but also in macrophages that had infiltrated the lamina propria (Lee et al, 2000).…”
Section: Introductionmentioning
confidence: 97%